1998
DOI: 10.1002/(sici)1096-9861(19980831)398:3<420::aid-cne8>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the neuronal transferrin receptor is age dependent and susceptible to iron deficiency

Abstract: In order to characterize the mechanism by which Iron (Fe) is taken up by neurons, we examined the neuronal expression of transferrin receptor (TR) in rats during development and iron (Fe) deficiency by using immunohistochemistry, in vitro receptor autoradiography and in situ hybridization. In contrast to the continuous expression of TR in brain capillary endothelial cells regardless of the age of the animals studied, the expression of neuronal TR was almost absent at late embryonic and early postnatal ages but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 33 publications
5
67
0
2
Order By: Relevance
“…The main players of cellular iron homeostasis comprise: the transferrin receptor (Griffiths and Crossman 1996;Moos et al 1998), the divalent metal transporter DMT1 (Burdo et al 1999(Burdo et al , 2001Williams et al 2000), the iron storage protein ferritin (Benkovic and Connor 1993), and the iron export transporter ferroportin (Wu et al 2004), all of which are well expressed in different areas of the brain. In the particular case of DMT1, which mediates ferrous iron uptake into cells (Gunshin et al 1997), in situ hybridization studies in developing rat brain showed DMT1 mRNA localization in striatum, cortex, hippocampus, and cerebellum (Williams et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The main players of cellular iron homeostasis comprise: the transferrin receptor (Griffiths and Crossman 1996;Moos et al 1998), the divalent metal transporter DMT1 (Burdo et al 1999(Burdo et al , 2001Williams et al 2000), the iron storage protein ferritin (Benkovic and Connor 1993), and the iron export transporter ferroportin (Wu et al 2004), all of which are well expressed in different areas of the brain. In the particular case of DMT1, which mediates ferrous iron uptake into cells (Gunshin et al 1997), in situ hybridization studies in developing rat brain showed DMT1 mRNA localization in striatum, cortex, hippocampus, and cerebellum (Williams et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Transferrin receptor (TfR) expression was decreased in the lumbar spinal cords of double transgenic mice from the presymptomatic stage through end-stage. Because TfR is expressed predominantly on neurons [47][48][49], the decrease could reflect the loss of neurons in the SOD1 and double transgenic mice. However, TfR is a cellular iron uptake protein and its expression is post-transcriptionally regulated by cellular iron status.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor is primarily localized to gray matter rather than white matter. Immunoreactivity in neurons is apparent as early as birth and reaches maximal levels at postnatal day 21 (Moos et al, 1998). Oligodendrocytes, which express the highest levels of iron in the brain, may not play a significant role in iron delivery given the preferential distribution of the transferrin receptor in the gray matter (Moos et al, 1998).…”
Section: Transferrinmentioning
confidence: 99%